The Effect of Flexible Working Arrangement and Work Life Balance on Employee Performance - Thaufayl, Muhammad Hilmana Chaska; Ardyanto, Muhammad Farrel; Julio, Farrel Lucky; Nugroho, Albertus Aldo; Pratama, Husein Mizar (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research investigates the impact of Work Motivation and Job Compensation on employee performance. The findings affirm that Work Motivation and Job Compensation exert a strong influence, fostering enhanced performance. While approximately one-third of the variation in performance can be explained by these factors, the majority is influenced by unaccounted variables. In essence, enhancing Work Motivation and Job Compensation proves pivotal for boosting employee productivity. For future research, it is recommended to explore additional variables. For practitioners, human resource management strategies involving incentives, employee satisfaction surveys, and staff development can elevate team performance. The finding in this study provides valuable insights into the factors influencing employee performance, offering organizations the opportunity to maximize their human resources potential.